Conflict adaptation during multilingual language production as evidenced by the n-3 effect. Issue 1 (27th January 2021) - Declerck, Mathieu; Schuch, Stefanie; Philipp, Andrea M.
Abstract: Several multilingual language production models assume that language control is instigated by conflict monitoring. In turn, conflict adaptation, a control process which makes it easier to resolve interference if previously a high-interference context was detected, should also occur during multilingual production, as it is triggered by conflict monitoring. Because no evidence has been provided for conflict adaptation in the multilingual production literature, we set out to investigate this process using the n-3 effect. Our study showed that the n-3 effect can be observed during multilingual production, and thus provides evidence for conflict adaptation during multilingual production.